ANALYSIS OF THE USE OF TRADITIONAL FOOD AS A THEMATIC LEARNING RESOURCE IN PRIMARY SCHOOLS - Herlina, Herlina; Nursakina, Nursakina (JURNAL PENDIDIKAN GLASSER, 2024)
Education is rooted in national culture. In reality, we still find learning that does not integrate local culture as a learning resource. This research aims to explore local culture, especially traditional food, as a learning resource, by exploring its potential based on the curriculum used in elementary schools. This research uses a qualitative approach with a phenomenological design. The subjects of this research were traditional food sellers, a teacher and fourth grade students at SDN Padalaa who were determined based on purposive sampling techniques. The data collection techniques used were observation, interviews, documentation and literature study. This research uses data analysis techniques, namely data reduction, data presentation and drawing conclusions. The research results show that of the nine learning themes for class IV, there are four themes that can integrate Tolimbu and Juada traditional food as learning resources or 44.4% of all existing themes. The conclusion of this research is that the potential for traditional food as a learning resource in thematic learning at Padalaa Elementary School, Morowali Regency is very large for teachers to continue to develop